Wideband Wide-Scan Tightly Coupled Dipole Array - Wang, Ya-Ru; Zhu, Qingchao; Fang, Jia; Zhang, Xiaolin (Proceedings (IEEE International Symposium on Microwave, Antenna, Propagation and EMC Technologies for Wireless Communications. Online), 2024)
In this paper, a wideband, wide-scan tightly coupled dipole array (TCDA) is designed. The dipole elements and integrated strip line balun are printed on a vertical printed circuit board (PCB) backed with a ground plane. The use of strip line balun can effectively broaden the bandwidth of antenna units and eliminate standing wave singularities within the working band. A wide-angle impedance matching (WAIM) layer printed with defective rings over the array aperture is used to achieve broadband and wide-angle scanning. The antenna is excited by a coaxial line with 50Ω characteristic impedance. Simulated results show that the design provides a 5:1 (from 2 GHz to 10 GHz) bandwidth while scanning to ±60° in E/H-plane, subject to VSWR < 3.